INTERDISCIPLINARY STRATEGIES IN EDUCATION WITH PRAGMATIC VARIATIONS - Khalifa Paluanova (Web of Journals Publishing, 2024)
This article delves into the challenges and strategic approaches associated with teaching pragmatic variation in language education. Drawing insights from the interdisciplinary intersections of pragmatics, linguistics, and didactics, it emphasizes the dynamic nature of language within diverse social, cultural, and situational contexts. The exploration explores nuanced linguistic challenges, cultural influences, and the imperative role of educators in fostering holistic language proficiency. By advocating for contextualized learning, cultural sensitivity training, technology integration, and collaborative methods, the study positions pragmatic variation as a cornerstone for developing communicators capable of navigating the intricacies of global communication effectively.
Keywords: pragmatic variation, language education, cultural sensitivity, contextualized learning, linguistic proficiency, interdisciplinary approach, global communication.